2018
DOI: 10.1002/jsfa.9429
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antioxidative properties of different parts of garden rhubarb, blackcurrant, chokeberry and blue honeysuckle

Abstract: BACKGROUND: It is important to find plant materials that can inhibit the growth of Listeria monocytogenes and other food-spoiling bacteria both in vitro and in situ. The aim of the study was to compare antibacterial and antioxidative activity of selected plant-ethanol infusions: leaves and berries of blackcurrant (Ribes nigrum L.), berries of chokeberry (Aronia melanocarpa (Michx.) Elliott) and blue honeysuckle (Lonicera caerulea L. var. edulis); petioles and dark and light roots of garden rhubarb (Rheum rhapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 33 publications
(50 reference statements)
2
36
0
Order By: Relevance
“…The higher TOC values in the samples treated with BCleaves, tomato, and BHSberries can also be explained by LA oxylipins originating from blackcurrant leaves or tomato seeds [34] and cuticles, rich in unsaturated fatty acids, particularly linoleic acid. Compared to chokeberry and blackcurrant berries, blue honeysuckle berries do not contain delphinidin [13], which possesses a slightly higher antioxidant activity than cyanidin, owing to the presence of vicinal OH groups [35]. Altogether, tomato, rhubarb petioles, and blue honeysuckle berries exerted a pro-oxidative effect in meat mixtures (high TOC and MDA values, Figure 5A,C).…”
Section: Fatty Acid Oxidationmentioning
confidence: 97%
See 4 more Smart Citations
“…The higher TOC values in the samples treated with BCleaves, tomato, and BHSberries can also be explained by LA oxylipins originating from blackcurrant leaves or tomato seeds [34] and cuticles, rich in unsaturated fatty acids, particularly linoleic acid. Compared to chokeberry and blackcurrant berries, blue honeysuckle berries do not contain delphinidin [13], which possesses a slightly higher antioxidant activity than cyanidin, owing to the presence of vicinal OH groups [35]. Altogether, tomato, rhubarb petioles, and blue honeysuckle berries exerted a pro-oxidative effect in meat mixtures (high TOC and MDA values, Figure 5A,C).…”
Section: Fatty Acid Oxidationmentioning
confidence: 97%
“…In this study, BCleaves had no inhibitory effect on microbial growth. Our previous in vitro study [13] found that petioles and the roots of garden rhubarb had a high antibacterial and antioxidative activity and suggested them as good candidates to use in meat products. Obviously, not always the promising results of in vitro studies are repeatable in food matrices.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 3 more Smart Citations